Docosahexaenoic Acid and Nervonic Acid Synergically Enhance Cognitive Memory in Normal Mice via Brain Fatty Acids Remodeling - Hai‐Yan Ou; Lei Feng; Rui‐Ye Chen; Hui‐Yun Lu; Shuang Cai; Zhi‐You Yang (eFood)
ABSTRACT Docosahexaenoic acid (DHA) and nervonic acid (NA) are the main components of brain gray and white matter, respectively. Preclinical and clinical studies suggest the effects of DHA or NA supplementation on memory improvement in aging and Alzheimer's disease models. However, it is not yet clear whether dietary supplementation with DHA and NA can enhance memory by increasing their levels in gray and white matter. The present study aimed to examine the spatial memory and brain white and gray matter lipidomic profiles in adolescent mice with or without a DHA and NA‐enriched diet. Spatial memory and conditional fear memory were evaluated in adolescent mice using the Morris Water Maze and passive avoidance test beginning at 7‐week of age and mice were killed at 13‐week of age to allow for the dissection of brain tissues. Combined low dose treatment of DHA (600 mg/kg) and NA (94 mg/kg) synergically enhanced spatial memory and fear memory function, and the effects were better than that of DHA intervention. While, high dose of DHA and NA treatment was detrimental to long‐term spatial memory and fear memory, corresponding to the decreased levels of serotonin (5‐HT) in the cortex and hippocampus, and imbalanced fatty acids in the white and gray matter. In addition, c‐Fos positive neurons were increased in low dose DHA treated mice comparing to that of control mice. Lipidomic analyses suggest levels of NA, dihomo‐γ‐linolenic acid, EPA, DHA, and linoleic acid were increased in the white matter post low dose of DHA + NA treatment, as well as increased levels of dihomo‐γ‐linolenic acid, EPA, and DHA in the gray matter compared with control mice. Understanding how DHA and NA supplementation during the adolescent periods affects cognitive function in a dose‐specific manner has important implications for determining the dietary requirements of DHA and NA. The present study reported for the first time that DHA and NA combination regulate spatial memory in a dose‐specific manner and provides evidence that further research needs to consider how different ratios of DHA and NA regulate the fatty acid composition in white and gray matter, thereby influencing memory function.